High-Resolution Melting Curve Analysis, a Rapid and Affordable Method for Mutation Analysis in Childhood Acute Myeloid Leukemia - Liu, Yin; Tang, Jingyan; Wakamatsu, Peter; Xue, Huiliang; Chen, Jing; Gaynon, Paul S.; Shen, Shuhong; Sun, Weili (Frontiers in Pediatrics, 2014)
Background: Molecular genetic alterations with prognostic significance have been described in childhood acute myeloid leukemia (AML). The aim of this study was to establish cost-effective techniques to detect mutations of FMS-like tyrosine kinase 3 (FLT3), nucleophosmin 1 (NPM1), and a partial tandem duplication within the mixed-lineage leukemia (MLL-PTD) genes in childhood AML. Procedure: Ninety-nine children with newly diagnosed AML were included in this study. We developed a fluorescent dye SYTO-82 based high-resolution melting (HRM) curve analysis to detect FLT3 internal tandem duplication (FLT3-ITD), FLT3 tyrosine kinase domain (FLT3-TKD), and NPM1 mutations. MLL-PTD was screened by real-time quantitative PCR. Results: The HRM methodology correlated well with gold standard Sanger sequencing with less cost. Among the 99 patients studied, the FLT3-ITD mutation was associated with significantly worse event-free survival (EFS). Patients with the NPM1 mutation had significantly better EFS and overall survival. However, HRM was not sensitive enough for minimal residual disease monitoring. Conclusion: High-resolution melting was a rapid and efficient method for screening of FLT3 and NPM1 gene mutations. It was both affordable and accurate, especially in resource underprivileged regions. Our results indicated that HRM could be a useful clinical tool for rapid and cost-effective screening of the FLT3 and NPM1 mutations in AML patients.